Invasive wild pigs in North America : ecology, impacts, and management - VerCauteren, Kurt C.; Beasley, James C.; Ditchkoff, Stephen S.; Mayer, John J.; Roloff, Gary J.; Strickland, Bronson Keith, 1970- (Boca Raton : CRC Press, 2020)
"Wild pigs are an emerging issue as populations in North America and across the globe have grown very quickly in recent decades. Along with wild pigs come a multitude of costs that outweigh benefits. Feral swine cause significant damage to agriculture, livestock, natural resources, human safety, and property. This book covers all aspects of feral swine biology, ecology, history, strategies for management, as well as environmental and agricultural impacts. Current swine research demonstrates that a lack of control intervention results in significant damages and risks to important natural and agricultural resources"--
OCLC-licensed vendor bibliographic record.
Keywords: Wild boar -- North America; Feral swine -- North America; Wildlife pests -- Control -- North America; Introduced organisms -- Control -- North America; NATURE / Ecology; SCIENCE / Life Sciences / Zoology / General; SCIENCE / Life Sciences / General